Cancer risks in the workplace: better regulation, stronger protection - Musu, Tony; Vogel, Laurent; Wriedt, Henning (Brussels, 2016)
"In the context of the announced revision of the directive on carcinogenic substances, this publication reviews the limitations of the existing legislation and outlines the priorities for its reform.